Co‐occurrence of neurofibromatosis type 1 and optic nerve gliomas with autosomal dominant polycystic kidney disease type 2 - Peces, Ramón (Mol Genet Genomic Med, 2020)
BACKGROUND: Autosomal dominant polycystic kidney disease (ADPKD) and neurofibromatosis type 1 (NF1) are both autosomal dominant disorders with a high rate of novel mutations. However, the two disorders have distinct and well‐delineated genetic, biochemical, and clinical findings. Only a few cases of coexistence of ADPKD and NF1 in a single individual have been reported, but the possible implications of this association are unknown. METHODS: We report an ADPKD male belonging to a family of several affected members in three generations associated with NF1 and optic pathway gliomas. The clinical diagnosis of ADPKD and NF1 was performed by several image techniques. RESULTS: Linkage analysis of ADPKD family was consistent to the PKD2 locus by a nonsense mutation, yielding a truncated polycystin‐2 by means of next‐generation sequencing. The diagnosis of NF1 was confirmed by mutational analysis of this gene showing a 4‐bp deletion, resulting in a truncated neurofibromin, as well. The impact of this association was investigated by analyzing putative genetic interactions and by comparing the evolution of renal size and function in the proband with his older brother with ADPKD without NF1 and with ADPKD cohorts. CONCLUSION: Despite the presence of both conditions there was not additive effect of NF1 and PKD2 in terms of the severity of tumor development and/or ADPKD progression.